THE INFLUENCE OF NOVELTY SEEKING, INTEGRITY, CONSUMPTION STATUS ON INTENTION TO PURCHASE LUXURY COUNTERFEIT PRODUCTS WHICH IS MEDIATED BY ATTITUDE TOWARDS ITEMS - Melly Wahyundari; Nurainun; Khairina; Heriyana (RADJA PUBLIKA, 2025)
This study aims to examine whether attitude toward counterfeit goods mediates the relationship between novelty seeking, integrity, status consumption, and purchase intention for luxury counterfeit products. The study employs primary data collected through questionnaires distributed to 161 respondents selected using purposive sampling. The data analysis method used in this study is SEM-PLS with the help of WrapPLS 8.0 software. To assess data validity, the researchers employed convergent validity, discriminant validity, average variance extracted (AVE), reliability tests, goodness of fit, coefficient of determination (R2), Q-square coefficient, and effect size. The findings reveal that novelty seeking and status consumption significantly influence purchase intention for luxury counterfeit products, while integrity does not. The mediation analysis shows that attitude toward counterfeit goods mediates the influence of integrity and status consumption on purchase intention for luxury counterfeit products. However, the mediation analysis for novelty seeking does not yield significant results.